Guidance for Designing Effective Arabic Reading Teaching Materials - Nurhibbulwalidan, Nurhibbulwalidain; Fitri, Chusna Nazilatul; Salsabila, Arini; Karomah, Wasiatul; Haris, Abdul (IJIE International Journal of Islamic Education, 2024)
This study aims to describe how to design teaching materials that effectively support the learning of Arabic reading skills. This research uses a qualitative approach with a library research method. Data collection involves searching for sources from various references such as books, magazines, journals, literature, and existing research that can be deemed appropriate sources for the study. The data is described and elaborated based on several expert opinions. The data analysis technique used is content analysis. The benefit of this writing is to provide readers with insights into the guidelines for designing Arabic reading teaching materials. The research results indicate the necessity of designing effective qira'ah teaching materials. Consequently, students can easily understand the content of Arabic texts, grasp the material being taught, improve their reading skills, and efficiently complete the questions given after using Arabic teaching materials with the qira'ah method.